Monetization Management in Restaurant Business - Ivan D. Kotliarov (Техника и технология пищевых производств)
Introduction. The traditional model of restaurant business demonstrates an asymmetry between the structure of the complex service provided by restaurants and the structure of the customer payments, as restaurants normally charge only the price of meals while providing customers with a place for eating and offering them waiter services. This asymmetry creates mutual misunderstanding between restaurants and customers and undermines the performance of restaurants. Therefore, it creates a demand for a new model of monetization of restaurant service that would take into account the complex nature of these services. Study objects and methods. The paper reviews the existing practice of restaurant business. It focuses on the case study of the True Cost restaurant chain (Moscow, Russia), which is a typical example of the “true cost” model. Models of monetization are structured on the basis of strategic matrices method. Results and discussion. The author described the non-economic and economic tools that can be used to capture the value created by the complex restaurant service and built a hierarchical model of monetization system. The “true cost” monetization model sets up separate prices for meals and dining room. The economic nature of this model presupposes a direct link between elements of customers’ payments, elements of the complex service provided by restaurants, and elements of cost – fixed and variable. The author defined advantages and disadvantages of the “true cost” model and assessed the possibility of using it in other sectors of service industry. The paper also introduces a structured system of monetization models in restaurant business. Conclusion. The tradition monetization model blurs the nature of the restaurant services and reduces the financial results. Restaurants should implement monetization models that valorize all elements of the complex service. This goal can be chieved by pricing different elements of the complex service separately.